Repair of Rat Sciatic Nerve Defects by Using Allogeneic Bone Marrow Mononuclear Cells Combined with Chitosan/Silk Fibroin Scaffold. Issue 5 (May 2016) - Yao, Min; Zhou, Yi; Xue, Chengbin; Ren, Hechun; Wang, Shengran; Zhu, Hui; Gu, Xingjian; Gu, Xiaosong; Gu, Jianhui
The therapeutic benefits of bone marrow mononuclear cells (BM-MNCs) in many diseases have been well established. To advance BM-MNC-based cell therapy into the clinic for peripheral nerve repair, in this study we developed a new design of tissue-engineered nerve grafts (TENGs), which consist of a chitosan/fibroin-based nerve scaffold and BM-MNCs serving as support cells. These TENGs were used for interpositional nerve grafting to bridge a 10-mm-long sciatic nerve defect in rats. Histological and functional assessments after nerve grafting showed that regenerative outcomes achieved by our developed TENGs were better than those achieved by chitosan/silk fibroin scaffolds and were close to those achieved by autologous nerve grafts. In addition, we used green fluorescent protein-labeled BM-MNCs to track the cell location within the chitosan/fibroin-based nerve scaffold and trace the cell fate at an early stage of sciatic nerve regeneration. The result suggested that BM-MNCs could survive at least 2 weeks after nerve grafting, thus helping to gain a preliminary mechanistic insight into the favorable effects of BM-MNCs on axonal regrowth.